Psychometric properties of the COVID-19 related Perceived Stress Scale online version in the Spanish population - Becerra-García, Juan Antonio; Valdivieso, Irene; Barbeito, Sara; Calvo, Ana; Sánchez-Gutiérrez, Teresa (Journal of Affective Disorders Reports, 2024)
Objective: In Spain, there is no detailed information on the psychometric characteristics of the COVID-19 related Perceived Stress Scale (PSS-10-C). This study aimed to examine the psychometric properties of the PSS-10-C in the general Spanish population. Methods: The sample was selected using a non-probabilistic incidental sampling method. A psychometric study was performed with 290 participants (18–65 years). We used the PSS-10-C and an ad-hoc sociodemographic questionnaire. These instruments were administered in an online format. The data was collected between March and April 2021. Internal consistency, exploratory and confirmatory factor analysis, and K-means cluster analysis were carried out. Results: The PSS-10-C presented good internal consistency (α = 0.87) and a unidimensional structure of 10 items (which explained 46.1 % of the variance). We identified a cut-off point ≥ 26 as a reference for high-perceived stress and, consequently, identified that 5.9 % of the participants had high levels of COVID-19 related-stress. Conclusions: The PSS-10-C may be a helpful tool for assessing the general Spanish population's perceived stress associated to COVID-19. This preliminary study may be of interest for Spanish health professionals since report the specific PSS-10-C psychometric characteristics in the local population. It would be necessary to deepen into the psychometric study of the scale (i.e., examining convergent and discriminant validity).
Keywords: mental health; stress; psychological distress; COVID-19; general population; Scopus